Zircon M257 - a homogeneous natural reference material for the ion microprobe U-Pb analysis of zircon - Nasdala, L.; Hofmeister, W.; Norberg, N.; Mattinson, J. M.; Corfu, F.; Dörr, W.; Kamo, S. L.; Kennedy, Allen K.; Kronz, A.; Reiners, P. W.; Frei, D.; Kosler, J.; et al. (Blackwell publishing, 2008)
We introduce and propose zircon M257 as a future reference material for the determination of zircon U-Pb ages by means of secondary ion mass spectrometry. This light brownish, flawless, cut gemstone specimen from Sri Lanka weighed 5.14 g (25.7 carats). Zircon M257 has TIMS-determined, mean isotopic ratios (2s uncertainties) of 0.09100+_ 0.00003 for 206pb/238U and 0.7392+_0.0003 for 207pb/235U. Its 206pb/238U age is 561.3+_0.3 Ma (unweighted mean, uncertainty quoted at the 95% confidence level); the U-Pb system is concordant within uncertainty of decay constants. Zircon M257 contains ~ 840 μg g-1 U (Th/U ~ 0.27). The material exhibits remarkably low heterogeneity, with a virtual absence of any internal textures even in cathodoluminescence images. The uniform, moderate degree of radiation damage (estimated from the expansion of unit-cell parameters, broadening of Raman spectral parameters and density) corresponds well, within the "Sri Lankan trends", with actinide concentrations, U-Pb age, and the calculated alpha fluence of 1.66 x 1018 g-1. This, and a (U+Th)/He age of 419+_9 Ma (2s), enables us to exclude any unusual thermal history or heat treatment, which could potentially have affected the retention of radiogenic Pb. The oxygen isotope ratio of this zircon is 13.9%o VSMOW suggesting a metamorphic genesis in a marble or calc-silicate skarn.